Limiting distribution of time averages for the additive functionals preset on the semi-Markovian process - Eleiko, Ya. I. (Ukrains’kyi Matematychnyi Zhurnal, 1990)
We consider an additive functional ζ_t on a continuous time semi-Markov process with an arbitrary state space. We study the existence of the limiting distribution of ζ_t/t without the condition of the finiteness of the mean occupation time of a fixed state.